STUDY ON THE KINETICS OF BIOMASS BLENDS DEWATERING AS A STAGE OF THERMAL DEGRADATION - Yaroslav ZASIADKO (Stefan cel Mare University of Suceava, 2017)
Solid biomass co-combustion with coal in industrial furnaces, including those of power plants, looks promising in terms of fuel base diversification and also presents a way to reduce significantly the emission of air harmful pollutants, particularly carbon dioxide. CO2resultingfrom biomass burning is environmentally neutral, since the same amount of carbon dioxide will be consumed at the next cycle of biomass photosynthesis. In case of the Ukrainian low reactive anthracite schtib used in such technology, the radical differences in the kinetic characteristics of co-fired fuels become critical issues. A significant difference in the attainable degree of fuel milling fineness due to the prohibitively high expense for solid biomass milling makes the problem more complicated. The values of biomass particle fineness are approximately 5…15 mm; whereas the fineness of pulverized coal reaches as low as 30...50mkm. The moisture and volatiles content for the fuel mentioned also differ noticeably. Therefore, the stages of these fuels burn out will be extremely complex in terms of various time scales of subsequent stages and their positioning in the furnace. The case becomes even more aggravated insofar the kinetic characteristic of the stages of biomass combustion arenot known yet in details. The present work is dedicated to the research into the kinetics of biomass blends demoisturizationand aimed at the deriving of the Arrhenius type equations, allowing to develop submodels of the demoisturization as an individual stage of biomass burn out for 3-D models.